Adaptive Mesh Numerical Solution of the Electromagnetic Flowmeter for Partially-Filled Pipes - Najem, Saleh Esmael; Rashak, Qais A.; Ismael, Muneer A. (Basrah Journal for Engineering Sciences, 2007)
Electromagnetic flowmeters measure flow rate of the electrically conducting liquids. Its operation is based on Faraday’s principle of induction. In many situations the pipe may be partially filled where in this case the analysis of the flowmeter equation is widely altered and the numerical solution may diverge. In this paper we have established a new numerical formulation, based on finite difference method, which adaptively refines the mesh until the desired solution converges to a certain accuracy. The representation of the flowmeter equations in the polar axis of the solution domain (cylindrical cut from it the empty portion) can result in the singularities in the solution. To avoid these singularities, the grids are shifted one half mesh width from the polar axis. The number of iterations that gives convergence is appreciably reduced via this numerical technique. The build algorithm of the adaptive numerical solution led us to determine, for each liquid level, the optimum angular position of the electrodes that gives maximum accuracy i.e. minimum sensitivity to the changes in the velocity profile of the liquid to be metered.